2013
DOI: 10.1371/journal.pone.0061120
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypes of Allo- and Autoimmune Antibody Responses to FVIII Characterized by Surface Plasmon Resonance

Abstract: Evidence of antibody isotype/subtype switching may provide prognostic value regarding the state of immune responses to therapeutic proteins, e.g. anti-factor VIII (FVIII) antibodies that develop in many hemophilia A patients, clinically termed “inhibitors”. A sensitive, high- information-content surface plasmon resonance (SPR) assay has been developed to quantify IgG subtype distributions and the domain specificity of anti-drug antibodies. Plasma samples from 22 subjects with an allo- or auto-immune reaction t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
25
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(27 citation statements)
references
References 43 publications
2
25
0
Order By: Relevance
“…69 Because they measure both inhibitory and non-inhibitory antibodies, they are not equivalent to and cannot be substituted for functional inhibitor assays. They may be used to screen specimens for those requiring inhibitor assays 65 or to confirm the presence of specific antibodies.…”
Section: | Inhibitor Measurement Methodsmentioning
confidence: 99%
“…69 Because they measure both inhibitory and non-inhibitory antibodies, they are not equivalent to and cannot be substituted for functional inhibitor assays. They may be used to screen specimens for those requiring inhibitor assays 65 or to confirm the presence of specific antibodies.…”
Section: | Inhibitor Measurement Methodsmentioning
confidence: 99%
“…The majority of patients with severe inhibitors develop a polyclonal response consisting of primarily IgG1 and IgG4 subclasses of antibody that inactivate FVIII via a type I pattern with linear, second order kinetics [10]. A recent study using sensitive surface plasmon resonance (SPR) to investigate subclass specific binding to FVIII demonstrated that early anti-FVIII immune response in AH patients is characterized by primarily IgG1 while the IgG4 subtype is produced later, suggesting the gradual development of a polyclonal response caused by repeated doses of antigen over time [13]. Interestingly, epitope specificity does not appear to correlate with specific isotypes, rather, it has been suggested that IgG class switching occurs after epitope specificity is determined [13,14].…”
Section: Characteristics Of Allo-and Auto-antibody Response To Fviiimentioning
confidence: 99%
“…Despite the difference in pathological outcome, anti-FVIII auto-antibodies isolated from patients with acquired hemophilia appear to be remarkably similar to allo-antibodies directed against FVIII. The polyclonal response is also characterized by IgG1 and IgG4 subclasses, and these share the same epitopes as anti FVIII allo-antibodies [13,16,17]. It has been suggested that the differences in FVIII binding kinetics and the manifestation of bleeding might be related to a preponderance of antibody specific for one FVIII epitope, rather than the mix of many epitopes observed in patients with congenital hemophilia that develop inhibitors [13,16].…”
Section: Characteristics Of Allo-and Auto-antibody Response To Fviiimentioning
confidence: 99%
See 2 more Smart Citations